Индуктивность, перестраиваемая электрическим полем - Semenov, A. A.; Usanov, D. A. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The possibility of creation of a miniature passive electrical field controlled inductive unit has been shown. The experimental dependences of such inductance on the control of operating voltage have been presented. The recommendations on practical application of the proposed inductive element's construction have been given.